microRNA-139-5p exerts tumor suppressor function by targeting NOTCH1 in colorectal cancer - Zhang, Lijing (BioMed Central, 2014)
BACKGROUND: miR-139-5p was identified to be significantly down-regulated in colon tumor tissues by miRNA array. We aimed to clarify its biological function, molecular mechanisms and direct target gene in colorectal cancer (CRC). METHODS: The biological function of miR-139-5p was examined by cell growth, cell cycle and apoptosis analysis in vitro and in vivo. miR-139-5p target gene and signaling pathway was identified by luciferase activity assay and western blot. RESULTS: miR-139-5p was significantly down-regulated in primary tumor tissues (P < 0.0001). Ectopic expression of miR-139-5p in colon cancer cell lines significantly suppressed cell growth as evidenced by cell viability assay (P < 0.001) and colony formation assay (P < 0.01) and in xenograft tumor growth in nude mice (P < 0.01). miR-139-5p induced apoptosis (P < 0.01), concomitantly with up-regulation of key apoptosis genes including cleaved caspase-8, caspase-3, caspase-7 and PARP. miR-139-5p also caused cell cycle arrest in G0/G1 phase (P < 0.01), with upregulation of key G0/G1 phase regulators p21(Cip1/Waf1) and p27(Kip1). Moreover, miR-139-5p inhibited cellular migration (P < 0.001) and invasiveness (P < 0.001) through the inhibition of matrix metalloproteinases (MMP)7 and MMP9. Oncogene NOTCH1 was revealed to be a putative target of miR-139-5p, which was inversely correlated with miR-139-5p expression (r = -0.3862, P = 0.0002). CONCLUSIONS: miR-139-5p plays a pivotal role in colon cancer through inhibiting cell proliferation, metastasis, and promoting apoptosis and cell cycle arrest by targeting oncogenic NOTCH1.